A Systematic Review to Clarify the Prognostic Values of CD44 and CD44+CD24- Phenotype in Triple-Negative Breast Cancer Patients: Lessons Learned and The Road Ahead - Abdoli Shadbad, Mahdi; Hosseinkhani, Negar; Asadzadeh, Zahra; Derakhshani, Afshin; Karim Ahangar, Noora; Hemmat, Nima; Lotfinejad, Parisa; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Oncology, 2021)
As a unique population of tumor bulk, cancer stem cells have been implicated in tumor relapse and chemoresistance in triple-negative breast cancer (TNBC). Therefore, understanding the phenotype of cancer stem cells can pave the way for introducing novel molecular targeted therapies for treating TNBC patients. Preclinical studies have identified CD44+CD24-/low as a cancer stem cell phenotype; however, clinical studies have reported seemingly controversial results regarding the prognostic values of CD44 and CD44+CD24-/low phenotype in TNBC patients. To critically review the clinicopathological significance and prognostic values of CD44 and CD44+CD24-/low phenotype in TNBC patients, the Scopus, Embase, PubMed, and Web of Science databases were systematically searched to obtain the relevant records published before 20 October 2020. Based on nine included studies, CD44 and CD44+CD24-/low phenotype are associated with inferior prognosis in TNBC patients. Moreover, these cancer stem cell markers have been associated with advanced tumor stage, increased tumor size, high tumor grade, lymph node metastasis in TNBC patients. Our evidence has also indicated that, unlike the treatment-naïve TNBC patients, the tumoral cells of chemoradiotherapy-treated TNBC patients can upregulate the CD44+CD24-/low phenotype and establish an inverse association with androgen receptor (AR), leading to the inferior prognosis of affected patients. In summary, CD44 and CD44+CD24-/low phenotype can be utilized to determine TNBC patients' prognosis in the pathology department as a routine practice, and targeting these phenotypes can substantially improve the prognosis of TNBC patients.